Methods for studying Covid-19 impacts on wildlife conservation policies and local livelihoods in Vietnam - Pham Thu Thuy; Tăng Thị, K.H.; Nguyễn Thị, K.N.; Đặng, H.P.; Dương, N.P.; Lê Thị, T.T. (Center for International Forestry Research, 2022)
Over the past 10 years, the Government of Vietnam has developed many policies towards wildlife conservation. The introduction of the Vietnam Forestry Development Strategy for 2021–2030 and vision to 2050 outlines strategies and priorities in biodiversity conservation and implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). However, effective implementation of these strategies requires context-relevant actions that address issues currently facing central and local governments and people.